Perioperative Blood Pressure Monitoring in Patients With Obesity. (March 2019) - Eley, Victoria A.; Christensen, Rebecca; Guy, Louis; Dodd, Benjamin
Abstract : Blood pressure monitoring plays a key part in the preoperative, intraoperative, and postoperative care of all patients. In patients with obesity, hypertension indicates increased metabolic and surgical risk and may signal the presence of significant medical comorbidities, including obstructive sleep apnea. Avoidance of hypertension postoperatively is necessary to minimize bleeding risk after surgery. Hypotension in the postoperative period may be the first sign of significant complications that require urgent management. With the problem of being overweight or obese now affecting two-thirds of adults in Western countries, the proportion of patients with obesity in perioperative environments is similarly increasing. Detection of aberrations in blood pressure is contingent on the accuracy of blood pressure measurement methods. Patients with obesity tend to have a large arm circumference and "cone-shaped arms." Standard blood pressure cuffs fit such patients poorly, and this compromises the accuracy of measurements. Alternatives to arm blood pressure cuffs, some made specifically for individuals with obesity, have been evaluated but are not widely available to clinicians. This focused narrative review will discuss the relevance of hypertension management in the care of patients with obesity, highlight the currently available methods for perioperative monitoring of blood pressure, and explore the opportunities that exist to improve the perioperative blood pressure care in patients with obesity undergoing surgical procedures.